1759 metų „Ziwato“ i ir priebalsinio kamieno daiktavardžiai ir jų raida - Vaičiakauskytė, Sonata (Baltistica, 2001)
i AND CONSONANT STEM NOUNS IN THE 1759 EDITION OF „ZIWATAS” AND THEIR EVOLUTIONThe following general conclusions can be made after a comparison of the declensions of i-stem nouns and consonant stem nouns in the „Ziwatas” dialect with the modern dialect of Kretinga. In the middle of the 18Ih century consonant stem nouns had still retained -en- and -er- endings, e.g. wąndeni 916, dukteryi 11218. Archaic singular and plural forms of the instrumental case of consonant stem nouns were found in the dialect of „Ziwatas”, e.g.akmemi I5819, ʃeʃermi 1215, wandemi 18428; akmemis 10221,ʃeʃermis 25418. The endings -ims and -yms = [ẹms] compete in the dative plural already in the middle of 18th century. Parallel use of these endings is characteristic of the modern speech of Kretinga as well. The edition of „Ziwatas" records no shortened plural forms of instrumental case with -imis. Two kinds of grammatical forms – shortened and with retention of the vowel in the ending – are used in the modern dialect of Kretinga. Older people use the aforementioned ending optionally. i-stem nouns in the dialect of „Ziwatas” still had the oldest plural form of the locative case with the ending -su.